Control technique of a V-shaped in-pipe robot composed of two underactuated roll-pitch joints. (16th February 2022) - Oka, Yoshimichi; Kakogawa, Atsushi; Tian, Yang; Ma, Shugen
Abstract : Conventional multilink articulated in-pipe inspection robots with elongated zig-zag structures are highly adaptive to a small diameter pipe. However, as more modules are connected, the longer the length of the robot becomes, it becomes more difficult to pass through complex-shaped pipes. We previously developed a robot that consists of minimized two-linked structures and realizes propulsive and rolling movements using two standard actuators through a simple miter-gear differential mechanism. Although less actuated design enables a short-length structure of the robot, a transformation method is necessary to change the robot's posture to switch both of the two movements. Thus, in this paper, we introduce a method of driving the underactuated roll-pitch joints through a speed difference between two motors. To adjust the multiple outputs distribution of our underactuated mechanism, many movements that can be generated by controlling the actuators' rotational directions and speeds in the links are described analytically. Among them, the effectiveness of three functional movements is verified experimentally. In addition, trials of the proposed robot in the out-of-plane double elbow will be conducted to demonstrate that the proposed V-shaped structure could pass through a 4-inch out-of-plane double elbow where the existing wheeled and crawler in-pipe robots cannot. GRAPHICAL ABSTRACT: UF0001